Simultaneous inter- and intra-group conflicts - Johannes Münster (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2004)
Lecture on the first SFB/TR 15 meeting, Gummersbach, July, 18 - 20, 2004: This paper models the trade-off between production and appropriation in the presence of simultaneous inter- and intra-group conflicts. The model exhibits a 'group cohesion effect ': if the contest between the groups becomes more decisive, or contractual incompleteness between groups becomes more serious, the players devote fewer resources to the intra-group conflict. Moreover, there is also a 'reversed group cohesion effect': if the intra-group contests become less decisive, or contractual incompleteness within groups becomes less serious, the players devote more resources to the inter-group contest. The model also sheds new light on normative questions. I derive exact conditions for when dividing individuals in more groups leads to more productive and less appropriative activities. Further, I show that there is an optimal size of the organization which is determined by a trade-off between increasing returns to scale in production and increasing costs of appropriative activities.
urn:nbn:de:bvb:19-epub-13542-9
Keywords: D72; D74; H11; H74; 330; Conflict; rent-seeking; federalism; hierarchy